Implementation of Differentiated Instruction in Natural and Social Sciences (IPAS) at SD Negeri Donomulyo, Kulon Progo - Wahyu Sudibyo; Victor Novianto; Esti Setiawati; Emi Tipuk Lestari; Sukadari (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aimed to describe the implementation of differentiated instruction in the Natural and Social Sciences (IPAS) subject at SD Negeri Donomulyo, Nanggulan Sub-district, Kulon Progo Regency. The research focused on planning, implementation, assessment, as well as the supporting and inhibiting factors of differentiated instruction. A qualitative approach with a case study design was employed. Research participants comprised a fifth-grade teacher, the school principal, fifth-grade students, parents, and the school committee chairperson. Data were collected through interviews, observation, and documentation. Data analysis followed the Miles, Huberman, and Saldaña interactive model, encompassing data condensation, data display, and conclusion drawing and verification. The findings indicated that the planning of differentiated instruction began with assessing students’ learning needs, including readiness, interests, and learning styles. Instruction was implemented by grouping students according to visual, auditory, and kinesthetic learning styles, with differentiation applied to content, process, and product. Assessment was conducted through diagnostic, formative, and summative measures in the form of process evaluation, tests, and product assessment. Supporting factors included the availability of facilities and infrastructure, support from the school principal, colleagues, the school committee, parents, and student enthusiasm. Inhibiting factors included time constraints, technical difficulties, challenges in determining appropriate forms of differentiation, budget limitations, and irregular in-service training. The study concluded that differentiated instruction in the IPAS subject had been implemented; however, further strengthening is needed in planning, strategy variation, assessment, and teacher competency development.